ETIOLOGY, SPREAD, CLINICAL MANIFESTATIONS, TREATMENT, AND PREVENTION OF INFLUENZA (Лучшие интеллектуальные исследования, 2024)
Influenza is a viral disease and one of the infectious diseases posing significant risks to human health. This illness is particularly widespread during the winter season and can lead to severe complications. Having comprehensive knowledge about the spread, causes, and preventive measures against influenza is crucial for everyone